Implementation of revised Baux Score to Predict Mortality Burn Injured Patients in Burn Unit of dr. Cipto Mangunkusumo General Hospital, Jakarta - Wardhana, Aditya; Mulyantara, Irwan; Kekalih, Aria (UI Scholars Hub, 2016)
Introduction. Implementation of stratification in burn injured patients referred to a very helpful approach for surgeon distinguishing severity of problems as well as predicting the outcome and lead a surgeon to make an accurate decision and a guidance to deliver patient’s condition to his/her family. A stratification tools for prediction should be simple and applicable in clinical setting. It also feasible to be applied for clinical use, research purpose, and system audit. Amongst scoring systems in burn surgery, revised Baux score is the one. The study is aimed to run validation in our burn characteristics. Method. A study run to find out validation for revised Baux score, prior to its use for application in our setting. We run cohort study enrolled burn injured patient treated during period of January 2010 to December 2012, retrospectively. Total body surface area involved, age and inhalation injury referred to variables subjected to statistical analysis. Results. Out of 442 burn injured patient, there were 234 subjects included in the study. Statistical analysis using Hosmer and Lemeshow test addressed to evaluate calibration of scoring performance showed p value of p = 1 (> 0.05), and for its precision we found the performance of discrimination of r–Baux score showed the area under curve (AUC) of 0.87 (CI 95%; 0.825–0.915), showing a p value of <0.001, and sensitivity 77.9% and specificity 76.9%. Conclusion. On validation, revised Baux score provide a good performance and likely would provide a merit of its clinical application.